Reply to Sagliocco, O.; Betelli, M. Comment on “Fierro et al. Severe Hypotension, Bradycardia and Asystole after Sugammadex Administration in an Elderly Patient. Medicina 2021, 57, 79” - Carmen Fierro; Alessandro Medoro; Donatella Mignogna; Carola Porcile; Silvia Ciampi; Emanuele Foderà; Romeo Flocco; Claudio Russo; Gennaro Martucci (Medicina, 2022)
We thank Dr. Sagliocco and Dr. Betelli for their comments [...]